Family Handling Stress during Lockdown in India - Ms. Pooja Shah, Prof. Rameshwari Pandya (Drugs and Cell Therapies in Hematology, 2021)
World Health Organization has declared the COVID-19 Pandemic in India. For safety purpose government announced lockdown and curfew for some time. Therefore people should have distance and safe. Family member live together and spend time with another. But time spent in four wall was also difficult. All member feel anxious, stressful and mentally disturbed. Thus, member have a recreational activities with family and friends spend maximum time in skillful activities.